Disrupted Development and the Future of Inequality in the Age of Automation - Schlogl, Lukas (Rethinking International Development series, 2020)
This open access book examines the future of inequality, work and wages in the age of automation with a focus on developing countries. The authors argue that the rise of a global 'robot reserve army' has profound effects on labor markets and economic development, but, rather than causing mass unemployment, new technologies are more likely to lead to stagnant wages and premature deindustrialization. The book illuminates the debate on the impact of automation upon economic development, in particular issues of poverty, inequality and work. It highlights public policy responses and strategies-ranging from containment to coping mechanisms-to confront the effects of automation.